COMPARISON BETWEEN CONCENTRIC BRACING FRAME AND ECCENTRIC BRACING FRAME IN EARTHQUAKE-RESISTANT HIGH-RISE BUILDINGS - Ahmed Aldaw Alhussein, Mohammedalameen; Wahiddin, Wahiddin; Suryadi, Akhmad (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2023)
Earthquake is a natural disaster that often occurs in Indonesia, so buildings must be designed according to earthquake regulations SNI 1726:2019 Seismic. The height of the building is based on the maximum limit according to SNI 1726:2012 table 9 and article 7.2.5.4. Based on these limitations, a size of 12 floors (48 meters) and eight floors (45.9 meters) in this study. Previous research has shown that ground motions were evaluated using the response-based damage model proposed by (Karsaz & Razavi Tosee, 2018). Then, the structures were rehabilitated with different bracing systems (eccentric and concentric inverted-V) and, again, their damage under earthquakes was evaluated and compared with those of moment resisting frames. The pushover analysis results while mid and high-rise buildings with Lateral shear force CBF is 0.91 %, whereas EBF is 2.77 %, compared to MRF. Therefore, CBF has a higher elastic stiffness than EBF. The bracing increases displacements for CBF by 70 % and EBF by 77% compared to MRF because EBF bracing decreases the displacements of the structural floors considerably; therefore, it can be said that the EBF bracings provide more lateral hardness for steel structures in comparison to the CBF bracings. The maximum inter-story drift CBF is 85%, while EBF is 86% for e = 0.50 m. Therefore, EBF is more malleable than CBF; the weight difference is 1.530%for CBF and 3.20 %for EBF compared to MRF. Therefore, EBF has a higher weight than CBF, the weight of the intended frames. There is little difference in the importance of the planned structures but the difference between their seismic performances under nonlinear static and dynamic. Using response-based damage models could be suitable for estimating the vulnerability of steel structures rehabilitated with a bracing system.